Lithium iron phosphate battery and preparation method and application thereof
By improving the battery structure design and electrolyte composition of lithium iron phosphate batteries, adopting a polyimide ceramic coating with staggered encapsulation and improving the separator, the problem of overcharge thermal runaway and fire of lithium iron phosphate batteries has been solved, thereby improving safety performance and meeting the safety standards of electric buses.
Patent Information
- Application Number
- CN202511129879.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-13
- Publication Date
- 2025-11-25
AI Technical Summary
Existing lithium iron phosphate batteries pose a risk of thermal runaway and fire during overcharging and are difficult to meet the safety standards for electric buses, especially during 1C overcharging for 12 minutes, which may result in short circuits and sparks.
By improving the battery structure design, a polyimide ceramic coating is used to cover the edge of the positive electrode and the negative electrode in a staggered manner. Combined with improvements to the separator and electrolyte composition, including the use of meta-aramid ceramic coating and specific additives, the short-circuit contact energy is reduced, thus preventing short-circuit arcing of the battery cell.
Extending the overcharge time reduces the probability of fire, ensuring that the battery cells do not catch fire or explode during overcharging, meeting the thermal runaway test requirements of electric bus safety standards, and improving the safety performance of the battery cells.
Smart Images

Figure CN121011699A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery new energy technology, specifically to a lithium iron phosphate battery, its preparation method, and its application. Background Technology
[0002] Commercial lithium-ion batteries are now widely used due to their energy density of 180-200 Wh / kg and a nominal cycle life of over 6000 cycles. Most mainstream new energy vehicles on the market currently use lithium-ion batteries, but the numerous car fires that occur annually have seriously impacted the customer experience. Therefore, the safety of lithium-ion batteries is a key concern within the new energy industry.
[0003] Regarding the mechanism of internal short circuits in lithium-ion batteries, numerous experiments and studies have shown that inside the battery, when heated, the separator shrinks and closes its pores, making it easy for electrical sparks to be generated when the metal foil comes into contact with the positive (negative) electrode coating. Additionally, during overcharging, the accumulation of heat in the electrolyte at higher voltages can also cause a series of safety risks. Therefore, from a lithium-ion battery safety design perspective, the design should avoid these risks.
[0004] For safety design considerations, especially for buses with large passenger capacities, the national standard GB 38032-2020 stipulates that electric bus batteries must undergo a 1C overcharge for 12 minutes before thermal runaway is triggered, and must not catch fire or explode. However, current research on thermal runaway in LFP lithium-ion batteries mostly focuses on system temperature rise warning and voltage protection, with few reports on methods to prolong thermal runaway by improving cell design and the composition of the separator and electrolyte. Therefore, based on existing research, how to further improve the overcharge thermal runaway of lithium iron phosphate batteries, extend the overcharge time, and reduce temperature rise and voltage remains a crucial and paramount consideration in the safety design of lithium-ion batteries. Summary of the Invention
[0005] The purpose of this invention is to provide a lithium iron phosphate battery, its preparation method and application. This lithium iron phosphate battery avoids contact between the positive and negative aluminum foils, reduces the energy of short-circuit contact, avoids short-circuit arcing of the cell, and further, by improving the composition of the separator coating and electrolyte, effectively prevents the occurrence of overcharge thermal runaway and fire in square lithium iron phosphate batteries, and extends the overcharge time.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a lithium iron phosphate battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte; The positive electrode sheet includes a positive current collector, a lithium iron phosphate positive active material layer disposed on the positive current collector, and a polyimide ceramic coating disposed at the edge of the positive current collector, and there is no gap between the positive active material layer and the polyimide ceramic coating. The negative electrode sheet includes a negative electrode current collector and a negative electrode active material disposed on the negative electrode current collector. The edge of the negative electrode sheet on the tab side is completely covered by the negative electrode active material with no blank current collector exposed. The edge of the polyimide ceramic coating on the top tab side of the positive electrode sheet is misaligned and covered with the edge of the tab side of the negative electrode sheet; The diaphragm includes a base membrane, a meta-aramid ceramic coating coated on both sides of the base membrane, and a water-based polyvinylidene fluoride (PVDF) coating coated on the meta-aramid ceramic coating. The electrolyte contains lithium salt, solvent, and additives, including fluorobenzene, biphenyl, and a third additive, wherein the third additive is lithium difluorophosphate and / or lithium difluoroborate.
[0007] Based on the above technical solutions, this invention, through improvements to the cell structure design, separator, and electrolyte composition, can extend the overcharge time and reduce the probability of fire. The cell does not catch fire or explode during overcharge, and the overcharge thermal runaway time meets the 12-minute requirement. The innovation of this invention lies mainly in how to prevent arcing failure in large-shell cells during 1C overcharge for 12 minutes, improving the cell's safety performance, further reducing the energy of short-circuit contact, avoiding short-circuit arcing, and preventing overcharge thermal runaway fires. As an example, the lithium iron phosphate battery is a square lithium iron phosphate battery.
[0008] In at least one embodiment of the present invention, the positive current collector is an aluminum foil; The width of the polyimide ceramic coating is 2-4 mm. This coating is made of a composite material of polyimide and ceramic powder, which is a high-thixotropic tab adhesive. This ceramic is heat-resistant, with a temperature resistance of approximately greater than 250°C. Polyimide replaces traditional polyvinylidene fluoride (PVDF). Compared to traditional PVDF ceramics, polyimide is less prone to peeling off at high temperatures and has higher heat resistance. This ceramic is heat-resistant, with a temperature resistance of approximately greater than 250°C. The width of the insulating ceramic layer is 6-9 mm, leaving a width of 2-4 mm after laser cutting. During process thermal runaway testing, after the diaphragm shrinks, the ceramic protection at the edge of the positive electrode prevents arcing when it contacts the negative electrode. Simultaneously, a certain thickness is applied to the tabs to increase the toughness at the base of the tabs. There is no gap between the positive electrode active material layer and the polyimide ceramic coating, that is, there is no gap between the positive electrode edge material area and the positive electrode material area, and the foil cannot be exposed. If there is a gap, after the diaphragm between the positive and negative electrodes shrinks, the exposed positive electrode foil will ignite the combustible gas after contacting the negative electrode material area. The gapless setting can avoid the diaphragm shrinking during overcharge thermal runaway test, and the foil igniting upon contact with the negative electrode material area.
[0009] In at least one embodiment of the present invention, the negative electrode current collector is a copper foil; The negative electrode active material is a carbon material, and more specifically, artificial graphite; The negative electrode adopts a cutting scheme, with the entire upper edge of the negative electrode sheet being cut off to ensure that there is no foil leakage at the upper edge. During the overcharge thermal runaway test, no negative electrode copper foil directly contacts the positive electrode material area or foil material, resulting in sparking and ignition of flammable gas.
[0010] In at least one embodiment of the present invention, with the tab side as the top, the entire edge of the tab side of the negative electrode sheet falls within the polyimide ceramic coating, and the edge of the polyimide ceramic coating of the positive electrode sheet falls above the edge of the tab side of the negative electrode sheet, that is, the edge of the positive electrode PI ceramic falls above the negative electrode sheet, while the ceramic edge at the top of the positive electrode falls on the material area of the negative electrode tab. In this invention, the phase difference of the electrode at the top of the core is covered by a staggered covering scheme. The laser-cut edge of the positive electrode PI ceramic and the laser-cut edge of the negative electrode material area are staggered by a certain distance. Because there are small molten beads on the laser-cut edge, the design prevents these metal foils from directly contacting each other and causing sparking. At the same time, this staggered covering design has a good improvement on the self-discharge of the cell.
[0011] In at least one embodiment of the present invention, the thickness of the base film is 5-7 μm, which has high wettability, small rupture area, and high rupture temperature (220°C), resulting in better safety performance in thermal needle penetration and overcharge thermal runaway. The base film is selected from one or more of PE film, PP film or PP / PE / PP composite film, polyimide film, polyvinylidene fluoride film, polyethylene nonwoven film, polypropylene nonwoven film, and polyimide nonwoven film. The thickness of the meta-aramid ceramic coating on each side is 2.5 to 3.5 μm, including but not limited to 3 μm; The meta-aramid ceramic coating, by weight percentage, is composed of 10% to 50% meta-aramid and 90% to 50% alumina, such as 10% meta-aramid and 90% alumina; under special proportions, it improves the high-temperature resistance and heat shrinkage performance of large-cell wound batteries. The thickness of the water-based PVDF coating on each side is 2.5 to 3.5 μm, including but not limited to 3 μm; As an example, the outermost layer of the thinner base film is a 3-micron aqueous PVDF layer, and the density of the adhesive layer is 0.6±0.1 g / m². 2 It maintains adhesion, improves bonding, and has a coating surface density of 7.5-9.5 g / m². 2 Breathability 7.5-8.5 S / 100ml, good heat shrinkage rate, heat shrinkage rate (%) at 200℃@1h MD2-2.5, TD2-2.5.
[0012] In at least one embodiment of the present invention, the fluorobenzene in the electrolyte has a mass percentage content of 2% to 4%, including but not limited to 2%; The biphenyl content in the electrolyte is 4% to 6% by mass, including but not limited to 4%; The third additive is lithium difluorophosphate and lithium difluoroborate, wherein the mass percentage of lithium difluorophosphate in the electrolyte is 0.2% to 0.5%, and the mass percentage of lithium difluoroborate in the electrolyte is 0.2% to 0.5%; for example, the mass percentage of lithium difluorophosphate in the electrolyte is 0.3%, and the mass percentage of lithium difluoroborate in the electrolyte is 0.3%. The electrolyte contains biphenyl and fluorobenzene additives that undergo electropolymerization reactions at approximately 4.5 V and 4.4 V, respectively. The battery voltage is limited to the reaction potential of the overcharge additive until all the additives have reacted. The third additive, lithium difluorophosphate (0.2%-0.5%), can inhibit HF corrosion, stabilize the polymer layer, and simultaneously improve cycle life. The second additive, lithium difluoroborate (0.2%-0.5%), acts as a gas-expansion synergist, which can suppress gas generation under high-temperature conditions of the battery cell and prevent the cell from bulging, thus avoiding affecting safety performance. Furthermore, based on the mass percentage in the electrolyte, the additives further include 3% to 4% (e.g., 3.5%) of vinylene carbonate, 0.4% to 0.6% (e.g., 0.5%) of methanedisulfonate (MMDS), 0.4% to 0.6% (e.g., 0.5%) of vinyl sulfate (DTD), and 0.4% to 0.6% (e.g., 0.5%) of fluoroethylene carbonate (FEC).
[0013] In at least one embodiment of the present invention, the lithium salt comprises lithium hexafluorophosphate (LiPF6) and lithium bis(fluorosulfonyl)imide (LiFSI); The concentration of LiPF6 in the lithium salt in the electrolyte is 0.8–0.9 mol / L, including but not limited to 0.8 mol / L; The concentration of LiFSI in the lithium salt in the electrolyte is 0.25–0.3 mol / L, including but not limited to 0.25 mol / L; The solvent is selected from one or more of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC). For example, based on the total weight of the solvent, the solvent consists of 25% EC, 30% EMC, and 45% DMC.
[0014] Secondly, the present invention provides a method for preparing a lithium iron phosphate battery as described in any of the preceding claims, comprising the following steps: S1. A positive electrode slurry is coated on the surface of the positive electrode current collector to form the positive electrode active material layer, and a polyimide ceramic coating is coated on the edge of the positive electrode current collector. The edge is laser-cut with tabs to obtain a positive electrode sheet of a specified width. S2. A negative electrode slurry is coated on the surface of the negative electrode current collector to form the negative electrode active material layer, and then laser-cut to obtain a negative electrode sheet of a specified width. S3. Battery assembly: The positive electrode and negative electrode are respectively rolled, cut, wound, assembled, placed in the shell, baked, injected with liquid, sealed, soaked, formed, aged and tested to obtain the lithium iron phosphate battery. In the winding process, the edge of the polyimide ceramic coating on the tab side of the positive electrode sheet is misaligned with the edge of the tab side of the negative electrode sheet to obtain a wound core electrode assembly. In the assembly and casing process, the electrolyte is injected after the electrode assembly is installed into the casing.
[0015] In at least one embodiment of the present invention, in step S1, the coating width of the polyimide ceramic coating is 6 to 9 mm, such as 6 mm; In step S2, the cutting width of the negative electrode sheet is 2-4 mm, such as 2 mm.
[0016] Thirdly, the present invention provides a method for improving the overcharge thermal runaway fire and extending the overcharge time of lithium iron phosphate batteries, wherein the lithium iron phosphate battery is prepared using any of the lithium iron phosphate batteries described above or the method described above.
[0017] The present invention has the following beneficial effects: This invention extends the overcharge time for thermal runaway during safety testing through battery design and process optimization, limits the voltage rise during the overcharge phase, reduces the energy of short-circuit contact and the probability of fire, and prevents the battery cell from sparking or catching fire during a short circuit. It can guarantee that the battery cell will pass the overcharge thermal runaway test in the national standard GB38032 100% and effectively improve the thermal runaway safety performance of the battery cell while meeting the relevant standards. Attached Figure Description
[0018] Figure 1This is a schematic diagram of the structure in Example 1 where the edge of the polyimide ceramic coating on the top tab side of the positive electrode sheet is misaligned with the edge of the top tab side of the negative electrode sheet. Figure 1 The numbers in the figure are marked as follows: 100 - positive electrode (Example 1), 101 - polyimide ceramic coating (Example 1), 200 - negative electrode (Example 1), 300 - separator (Example 1).
[0019] Figure 2 This is a schematic diagram of the structure of the edge of the PVDF ceramic coating on the top tab side of the positive electrode sheet and the covering of the top tab side of the negative electrode sheet foil in Comparative Example 1. Figure 2 The numbers in the figure are labeled as follows: 400 - positive electrode (Comparative Example 1), 401 - polyimide ceramic coating (Comparative Example 1), 500 - negative electrode (Comparative Example 1), 501 - negative electrode copper foil reserved area, 600 - separator (Comparative Example 1).
[0020] Figure 3 The voltage-time comparison curves are for Example 1 and Comparative Example 1.
[0021] Figure 4 The temperature-time comparison curves are for Example 1 and Comparative Example 1. Detailed Implementation
[0022] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0023] In the description of this invention, it should be noted that the terms "upper", "lower", "top", etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the system or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limiting this invention.
[0024] The present invention will now be described in further detail with reference to specific embodiments. The given embodiments are merely illustrative of the invention and not intended to limit its scope. The embodiments provided below can serve as a guide for further improvements by those skilled in the art and do not constitute a limitation on the invention in any way.
[0025] Unless otherwise specified, the methods used in the following embodiments are conventional methods, performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Unless otherwise specified, the materials and reagents used in the following embodiments are commercially available.
[0026] The polyimide ceramic coating used in the following examples is a composite material of polyimide and ceramic powder, with a mass fraction ratio of polyimide to ceramic (Al2O3) of 8:2 (the polyimide product name is ZONE12S-TS, manufacturer: Yanyi, and the boehmite (Al2O3) specification model is BG-611,365, manufacturer (Yishitong).
[0027] Example 1 I. Product Design like Figure 1 As shown, the square lithium iron phosphate battery provided in this embodiment includes a positive electrode (Example 1) 100, a negative electrode (Example 1) 200, a separator (Example 1) 300, and an electrolyte; The positive electrode sheet (Example 1) 100 includes a positive current collector aluminum foil, a lithium iron phosphate positive active material layer disposed on the aluminum foil, and a polyimide ceramic coating (Example 1) 101 with a width of 3 mm disposed at the edge of the positive current collector, and there is no gap between the positive active material layer and the polyimide ceramic coating. The negative electrode sheet (Example 1) 200 includes a negative current collector copper foil and a negative active material artificial graphite disposed on the copper foil. The edge of the tab side of the negative electrode sheet, i.e. the upper edge, is completely covered by the negative active material with no blank foil exposed. The edge of the polyimide ceramic coating on the top tab side of the positive electrode is offset from the edge of the top tab side of the negative electrode. Specifically, the edge of the top tab side of the negative electrode falls entirely within the polyimide ceramic coating, while the edge of the polyimide ceramic coating of the positive electrode falls above the edge of the top tab side of the negative electrode. The diaphragm (Example 1) 300 includes a PE base film with a thickness of 7 μm, a meta-aramid ceramic coating coated on both sides of the base film, and an aqueous PVDF coating coated on the meta-aramid ceramic coating. The thickness of the meta-aramid ceramic coating (10% meta-aramid and 90% alumina) on each side is 3 μm, and the thickness of the aqueous PVDF coating on each side is 3 μm. The electrolyte, by mass percentage, contains lithium salts, solvents, and additives. The solvent consists of EC 25% wt, EMC 30% wt, and DMC 45% wt. The lithium salts include LiPF6 (0.8M concentration in the electrolyte) and LiFSI (0.25M concentration in the electrolyte). The additives, by mass percentage in the electrolyte, include vinylene carbonate (VC) at 1.8% in the first electrolyte and 16% in the second electrolyte, for a total VC content of 3.5%. The high-temperature cycling stabilizer is 0.5% methane disulfonate (MMDS). The film-forming additives include DTD 0.5% and FEC 0.5%. Simultaneously added are 3% FB fluorobenzene, 5% LB biphenyl, 0.3% lithium difluorophosphate, and 0.3% lithium difluoroborate.
[0028] In this embodiment, the cell design steps are as follows: S1. Based on the external dimensions of the battery cell, determine the specific dimensional chain of the internal positive and negative electrode plates and the separator; The S2 positive and negative electrode intermediate insulating layer-insulating layer diaphragm adopts meta-aramid diaphragm, and the diaphragm selection and coating type are taken into design factors; S3. Electrolyte Design: Electrolyte additives and formulations are design factors for the system; S4. Negative electrode design: Add 3mm to the cutting width of the negative electrode calculated based on S1 as the design dimension for the negative electrode coating width; S5. Coating Design: A staggered design is adopted, in which the cutting edge of the negative electrode tab falls entirely in the middle of the ceramic area, and the ceramic edge of the positive electrode tab falls entirely on the cutting area of the negative electrode tab.
[0029] S6 Positive electrode design: The edge insulation layer type of the positive electrode is designed as the positive electrode design of the cell.
[0030] II. Process Design The square lithium iron phosphate battery was prepared according to the following steps: S1. A positive electrode slurry (lithium iron phosphate, formula LFP:Sp:CNT:PVDF=97.5%:0.42%:0.28%:1.8%) is coated on the surface of aluminum foil to form a positive electrode active material layer, and a polyimide ceramic coating is coated on the edge of the aluminum foil with a coating width of 6mm. The edge is laser-cut with tabs to obtain a positive electrode sheet with a specified polyimide ceramic coating width of 3mm. S2. Coat the surface of the copper foil with artificial graphite as a negative electrode paste to form the negative electrode active material layer. Then, laser cut the foil to a width of 2 mm to obtain a negative electrode sheet of a specified width. S3. Battery assembly: The positive electrode and negative electrode are respectively rolled, cut, wound, assembled, put into the shell, baked, injected, soaked, formed, aged, and then injected again, sealed and tested to obtain a square lithium iron phosphate battery. In the winding process, the edge of the polyimide ceramic coating on the top tab side is staggered and wrapped with the cutting edge on the top tab side of the negative electrode sheet to obtain the core electrode assembly. In the assembly and casing process, electrolyte is injected after the electrode assembly is installed in the casing.
[0031] Comparative Example 1 The difference from Example 1 is that the width of the PVDF ceramic coating on the aluminum foil is adjusted to 2mm, there is a 1mm gap between the positive electrode active material layer and the PVDF ceramic coating, the negative electrode sheet has a 0-1mm (greater than 0mm) negative electrode copper foil reserved area, the edge of the PVDF ceramic coating on the top tab side of the positive electrode sheet is conventionally covered with the negative electrode, only a ceramic coating is set on the separator, and the electrolyte does not contain fluorobenzene, biphenyl, lithium difluorophosphate and lithium difluoroborate, as detailed below: I. Product Design like Figure 2 As shown, the square lithium iron phosphate battery provided in this comparative example includes a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode sheet (Comparative Example 1) 400 includes a positive current collector aluminum foil, a lithium iron phosphate positive active material layer disposed on the aluminum foil, and a PVDF ceramic coating with a width of 2 mm disposed on the edge of the positive current collector, and there is a 1 mm gap between the positive active material layer and the PVDF ceramic coating. The negative electrode sheet (Comparative Example 1) 500 includes a negative electrode current collector copper foil and a negative electrode active material graphite disposed on the copper foil. After laser cutting, the negative electrode sheet has a 0-1mm (greater than 0mm) negative electrode copper foil reserved area 501. The edge of the PVDF ceramic coating on the tab side of the positive electrode sheet is wrapped with the conventional coating of the negative electrode. Specifically, on the tab side, the negative electrode foil wraps around the edge of the positive electrode ceramic, and on the non-tab side, the negative foil wraps around the positive foil. The diaphragm (Comparative Example 1) 600 includes a 7 μm thick base membrane PE layer, a 2 mm thick ceramic coating on the front side of the base membrane, and no other coating layers. The electrolyte, by mass percentage, contains lithium salts, solvents, and additives. The solvents consist of EC wt25%, EMC wt30%, and DMC wt45%. The lithium salts include LiPF6 (concentration in the electrolyte is 0.8M) and LiFSI (concentration in the electrolyte is 0.25M). The VC content in the first electrolyte is 1.8%, and the VC content in the second electrolyte is 16%, for a total VC content of 3.5%. The high-temperature cycling stabilizing additives are methylene disulfonate (MMDS) 0.5%, DTD 0.5%, and FEC 0.5%. There are no other additives. In this comparative example, the cell design steps are as follows: S1. Based on the external dimensions of the battery cell, determine the specific dimensional chain of the internal positive and negative electrode plates and the separator; The S2 positive and negative electrode intermediate insulating layer-insulating layer diaphragm uses a conventional ceramic diaphragm; S3. Electrolyte Design: Electrolyte additives and formulations are design factors for the system; S4. Negative electrode design: Based on the negative electrode design calculated in S1, the electrode is not cut into material, but rather produced as foil. S5. Coating Design: Adopting a conventional coating design, on the tab side, the negative electrode sheet coats the positive electrode 1-3mm, and the separator coats the negative electrode 2-3mm; on the non-tab side, the negative electrode coats the positive electrode 0.5-2mm. S6 Positive electrode design: The edge insulation layer type of the positive electrode is a standard mass production solution for PVDF.
[0032] II. Process Design The square lithium iron phosphate battery was prepared according to the following steps: S1. A positive electrode slurry (lithium iron phosphate, formula LFP:Sp:CNT:PVDF=97.5%:0.42%:0.28%:1.8%) is coated on the surface of aluminum foil to form a positive electrode active material layer. A PVDF ceramic coating is applied to the edge of the aluminum foil with a coating width of 2mm. The edge is laser-cut with tabs to obtain a positive electrode sheet of a specified width. There is a 1mm gap between the positive electrode active material layer and the PVDF ceramic coating. S2. Coat the surface of the copper foil with artificial graphite as a negative electrode paste to form the negative electrode active material layer. After laser cutting, retain a certain amount of negative electrode foil material, leaving a blank of 1mm. S3. Battery assembly: The positive and negative electrode sheets are rolled, cut, wound, assembled, placed in the shell, baked, injected with liquid, sealed, soaked, formed, aged and tested to obtain a square lithium iron phosphate battery. In the winding process, the conventional methods include negative electrode wrapping of positive electrode and diaphragm coating of negative electrode. In the assembly and casing process, the conventional electrolyte is injected after the electrode assembly is installed into the casing.
[0033] Performance test examples The batteries prepared in the above embodiments and comparative examples were subjected to performance tests, and the test standards were based on GB38032 "Safety Requirements for Electric Buses".
[0034] The experimental results are shown in Table 1. Figure 3 This is a voltage-time comparison curve. Figure 4 Temperature-time comparison curve.
[0035] Table 1. Results of Overcharge Thermal Runaway
[0036] The comparison results between Example 1 and Comparative Example 1 show that the overcharge voltage of the battery cell used in Comparative Example 1 increases sharply after about 532 seconds of overcharging, and the positive electrode material and negative electrode foil ignite upon contact, releasing heat and reaching a maximum temperature of 79-96 degrees Celsius. In Example 1, due to the influence of the electrolyte and the high temperature resistance of the separator, as well as the influence of the misaligned coating process, the overall ignition rate is reduced, the overcharge voltage is stabilized between 4-5V, and the overcharge time can meet 12 minutes.
[0037] In summary, this invention, through battery design and process optimization, can extend the overcharge time of thermal runaway during safety testing, limit the voltage rise during the overcharge stage, reduce the energy of short-circuit contact and the probability of fire, and prevent the cell from sparking or catching fire during short circuits, thus effectively improving the thermal runaway safety performance of the cell.
[0038] The present invention has been described in detail above. Those skilled in the art will recognize that the invention can be practiced in a wide range of ways with equivalent parameters, concentrations, and conditions without departing from its spirit and scope. While specific embodiments have been provided, it should be understood that further modifications can be made to the invention. In summary, according to the principles of the invention, this application is intended to include any changes, uses, or improvements to the invention, including modifications made using conventional techniques known in the art that depart from the scope disclosed herein.
Claims
1. A lithium iron phosphate battery, characterized in that, Includes positive electrode, negative electrode, separator and electrolyte; The positive electrode sheet includes a positive current collector, a lithium iron phosphate positive active material layer disposed on the positive current collector, and a polyimide ceramic coating disposed at the edge of the positive current collector, and there is no gap between the positive active material layer and the polyimide ceramic coating. The negative electrode sheet includes a negative electrode current collector and a negative electrode active material disposed on the negative electrode current collector. The edge of the negative electrode sheet on the tab side is completely covered by the negative electrode active material with no blank current collector exposed. The edge of the polyimide ceramic coating on the tab side of the positive electrode sheet is misaligned and covered with the edge of the tab side of the negative electrode sheet. The diaphragm includes a base membrane, a meta-aramid ceramic coating coated on both sides of the base membrane, and a water-based polyvinylidene fluoride coating coated on the meta-aramid ceramic coating. The electrolyte contains lithium salt, solvent, and additives, the additives including fluorobenzene, biphenyl, and a third additive, the third additive being lithium difluorophosphate and / or lithium difluoroborate.
2. The lithium iron phosphate battery according to claim 1, characterized in that: The positive current collector is aluminum foil; The width of the polyimide ceramic coating is 2 to 4 mm.
3. The lithium iron phosphate battery according to claim 1, characterized in that: The negative electrode current collector is a copper foil; The negative electrode active material is a carbon material, and more specifically, artificial graphite.
4. The lithium iron phosphate battery according to claim 1, characterized in that: With the tab side as the top, the entire edge of the tab side of the negative electrode sheet falls within the polyimide ceramic coating, and the edge of the polyimide ceramic coating of the positive electrode sheet falls above the edge of the tab side of the negative electrode sheet.
5. The lithium iron phosphate battery according to claim 1, characterized in that: The thickness of the base film is 5–7 μm; The base film is selected from one or more of PE film, PP film or PP / PE / PP composite film, polyimide film, polyvinylidene fluoride film, polyethylene nonwoven film, polypropylene nonwoven film, and polyimide nonwoven film. The thickness of the meta-aramid ceramic coating on each side is 2.5–3.5 μm; The meta-aramid ceramic coating, calculated by mass percentage, consists of 10%–50% meta-aramid and 90%–50% alumina. The thickness of the water-based polyvinylidene fluoride coating on each side is 2.5–3.5 μm.
6. The lithium iron phosphate battery according to claim 1, characterized in that: The fluorobenzene in the electrolyte has a mass percentage of 2% to 4%; The biphenyl content in the electrolyte is 4% to 6% by mass. The third additive is lithium difluorophosphate and lithium difluoroborate, wherein the mass percentage of lithium difluorophosphate in the electrolyte is 0.2% to 0.5%, and the mass percentage of lithium difluoroborate in the electrolyte is 0.2% to 0.5%. The additives, by mass percentage in the electrolyte, further include 3%–4% vinylene carbonate, 0.4%–0.6% methanedisulfonate, 0.4%–0.6% vinyl sulfate, and 0.4%–0.6% fluoroethylene carbonate.
7. The lithium iron phosphate battery according to claim 1, characterized in that: The lithium salts include lithium hexafluorophosphate (LiPF6) and lithium difluorosulfonyl imide (LiFSI); The concentration of LiPF6 in the lithium salt in the electrolyte is 0.8–0.9 mol / L; The concentration of LiFSI in the lithium salt in the electrolyte is 0.25–0.3 mol / L; The solvent is selected from one or more of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate.
8. The method for preparing a lithium iron phosphate battery according to any one of claims 1-7, characterized in that, Includes the following steps: S1. A positive electrode slurry is coated on the surface of the positive electrode current collector to form the positive electrode active material layer, and a polyimide ceramic coating is coated on the edge of the positive electrode current collector. The edge is laser-cut with tabs to obtain a positive electrode sheet of a specified width. S2. A negative electrode slurry is coated on the surface of the negative electrode current collector to form the negative electrode active material layer, and then laser-cut to obtain a negative electrode sheet of a specified width. S3. Battery assembly: The positive electrode and negative electrode are respectively rolled, cut, wound, assembled, placed in the shell, baked, injected with liquid, sealed, soaked, formed, aged and tested to obtain the lithium iron phosphate battery. In the winding process, the edge of the polyimide ceramic coating on the tab side of the positive electrode sheet is misaligned with the edge of the tab side of the negative electrode sheet to obtain a wound core electrode assembly. In the assembly and casing process, the electrolyte is injected after the electrode assembly is installed into the casing.
9. The method for preparing a lithium iron phosphate battery according to claim 8, characterized in that: In step S1, the coating width of the polyimide ceramic coating is 6-9 mm; In step S2, the cutting width of the negative electrode sheet is 2-4 mm.
10. A method for improving overcharge thermal runaway fire and extending overcharge time in lithium iron phosphate batteries, characterized in that, Lithium iron phosphate batteries are prepared using any one of the lithium iron phosphate batteries according to claims 1-7 or any one of the methods according to claims 8-9.
